Analisis Tingkat Pendidikan dan Pelatihan Karyawan Terhadap Kinerja Karyawan Home Industri Roti Solo Bakry - Syahrial Anwar Ferdian; Dini Yani; Puji Isyanto (Yayasan Daarul Huda Kruengmane, 2023)
In order to achieve the human resource management objectives that have been stated, human resources must be developed and maintained so that all organizational functions can run in balance. Human resource activities are part of the most central human resource management process and are a series in achieving organizational goals. The food and beverage industry is one of the industrial sectors that has an important role for economic growth in Indonesia. The food and beverage industry has the potential to become an industry that is relied upon for national economic growth because it has a lot of supply and demand. One of them is bread and other bakery products. Companies that are able to compete in the world market are companies that require good quality and quantity employee performance, achieved by an employee in carrying out his duties in accordance with the responsibilities that have been given. The performance of the Solo Bakry employees is the result of the efforts made by all components within the organization in achieving a common goal.